Ambiente construído e atividade física no tempo de lazer: uma análise em adultos atendidos na Atenção Primária à Saúde - Mello, Rafael Luciano de (2021)
Planning the built environment with favorable attributes to physical activity (PA) practice, is one of the investments that work to PA promotion at population level. However, examining this relationship in the context of Primary Health Care (PHC) users, who present different characteristics from the general population, is still unexplored in the literature. Therefore, the aim of this study was to analyze the association between the built environment attributes and leisure-time physical activity (LTPA) of adult PHC users in São José dos Pinhais city, southern Brazil. A quantitative, observational, cross-sectional study was conducted in 2019, with a representative sample of 615 adults (18-59 yrs) users of the PHC in the urban area of the city. Built environment attributes were evaluated using Geographic Information System (GIS) and included neighborhood characteristics (population density, residential density, average income area and street connectivity) as well the public open space (POS) exposure variables (presence, density and distance of six POS types – Sports and Leisure Centers, woods, Youth Recreational Center, free spaces, parks and squares) contained in a 500-meter network buffer around the participants’ homes. The LTPA was assessed with the International Physical Activity Questionnaire (IPAQ) to identify the leisure walking and moderate-to-vigorous physical activity (MVPA) levels at two cutoff points (≥ 10 min / wk; ≥ 150 min / wk), creating four outcomes. Multivariate Poisson regression was used to data analysis in the SPSS 24.0, keeping the significance level at 5%. The prevalence of some walking (≥ 10 min / wk) and MVPA (≥ 10 min / wk) was 25% and 21%, respectively. While the prevalence of walking and MVPA in recommended levels (≥ 150 min / wk) was 12% and 14%, correspondingly. The main results showed a positive association between population density, walking ≥ 150 min / wk (3rd tertile: PR: 1.75, 95% CI: 1.03-3.00, p<0.05) and MVPA ≥ 10 min / wk (3rd tertile: PR: 1.50, 95% CI: 1.04-2.16, p<0.05). The further distance to Youth Recreational Center was positively associated with walking ≥ 10 min / wk (3rd tertile: PR: 1.47, 95% CI: 1.04-2.09, p<0.05) as the Sports and Leisure Center presence was associated with walking ≥ 150 min / wk (PR: 1.77, 95% CI: 1.02-3.07, p<0.05). On the other hand, the free spaces presence was inversely associated with walking ≥ 10 min / wk (PR: 0.68, 95% CI: 0.48-0.95, p<0.05). In conclusion, higher population density, higher distance to the Youth Recreational Center and presence of Sports and Leisure Centers increased the prevalence of LTPA among Primary Health Care users, while having free spaces in the residential surrounding decreased the practice of walking. These results may assist the strategies of PA promotion adopted by policy makers and healthcare professionals in the Primary Health Care facilities.